Influence of calcium carbide formulations on growth, yield and nitrogen uptake of wheat under field conditions. (15th April 2016) - Mahmood, Rashid; Yaseen, Muhammad
ABSTRACT: Field experiments were conducted in 2006–2007 and 2007–2008 to evaluate the effects of three calcium carbide (CaC2 ) based formulations (slow release sources of acetylene and ethylene) - matrix-1 [(M-1)(21% CaC2, 58% polyethylene and 21% plaster of paris)], matrix-2 [(M-2)(42% CaC2, 48% polyethylene and 10% plaster of paris)] and paint coated [(PC)(35% CaC2, 44% paint and 21% plaster of paris)] - on nitrification inhibition; growth, yield and nitrogen (N)-uptake of wheat. All the three CaC2 formulations (CCF, s) inhibited nitrification, reduced plant height, and improved N-uptake, spike bearing tillers, 1000-grains weight and yield of Inqulab-91 and Bhakhar-02 wheat cultivars. Increase in grain yield was found maximum (22% over the control) with M-1 applied at 30 kg CaC2 ha −1 ; followed by M-2 and PC. Furthermore, CaC2 significantly reduced lodging in Bhakhar-02 plots. It is concluded that grain yield of wheat can be enhanced by the application of CaC2 formulations particularly M-1 along with NPK fertilizers.